A study of the status quo and favorable status of succession management deployment from the viewpoint of faculty members at Kermanshah university of medical sciences - Kalhori, Reza Pourmirza; Mousavi, Frank; Laei, Soosan; Shahsavari, Soodeh (International Journal of Engineering and Technology, 2018)
Successful succession management is one of the necessities in any organization, especially universities. In the management of higher education, succession planning deployment requires proprietary methods. Therefore, the present study aimed to investigate the status quo and favorable status of succession management deployment from the viewpoint of faculty members at Kermanshah University of Medical Sciences in 2017. In this descriptive-analytic and cross-sectional study, 95 faculty members were selected from the Departments of Basic Sciences and Clinical Sciences using nonrandom quota sampling. As for data collection, the Kim's succession planning questionnaire was employed. To analyze data, the SPSS Statistical Software Version 23.0 and the statistical tests of paired t-test, Chi-square and ANOVA were used to compare the status quo of succession management deployment with its favorable status and to study its decisive factors. The results of the present study revealed that there was a significant difference between the status quo and favorable status of t succession management deployment (P
Keywords: Management; Succession Management; Health-Oriented Organizations.